2000
DOI: 10.1021/bi0015562
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for P-Site Inhibition of Adenylyl Cyclase,

Abstract: P-site inhibitors are adenosine and adenine nucleotide analogues that inhibit adenylyl cyclase, the effector enzyme that catalyzes the synthesis of cyclic AMP from ATP. Some of these inhibitors may represent physiological regulators of adenylyl cyclase, and the most potent may ultimately serve as useful therapeutic agents. Described here are crystal structures of the catalytic core of adenylyl cyclase complexed with two such P-site inhibitors, 2'-deoxyadenosine 3'-monophosphate (2'-d-3'-AMP) and 2',5'-dideoxya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
124
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(130 citation statements)
references
References 34 publications
5
124
0
Order By: Relevance
“…2). However, the MANT group at the 2Ј-O-position did not confer high potency to compounds 21 and 22 because a polyphosphate chain is important for high inhibitor potency as well (25,27). MANT-ATP and MANT-ADP (compare compounds 6 and 8) were similarly potent C1⅐C2 inhibitors, whereas MANT-GTP was ϳ70-fold more potent than MANT-GDP (compare compounds 1 and 10).…”
Section: Potent and Selective Ac Inhibition By Mant-itp␥s Relative Tomentioning
confidence: 99%
See 2 more Smart Citations
“…2). However, the MANT group at the 2Ј-O-position did not confer high potency to compounds 21 and 22 because a polyphosphate chain is important for high inhibitor potency as well (25,27). MANT-ATP and MANT-ADP (compare compounds 6 and 8) were similarly potent C1⅐C2 inhibitors, whereas MANT-GTP was ϳ70-fold more potent than MANT-GDP (compare compounds 1 and 10).…”
Section: Potent and Selective Ac Inhibition By Mant-itp␥s Relative Tomentioning
confidence: 99%
“…However, ACT was the only cyclase studied that exhibited a higher V max in the presence of Mg 2ϩ than in the presence of Mn 2ϩ . In addition, the available literature evidence suggested that inhibitor sensitivity of cyclases in general is higher in the presence of Mn 2ϩ than in the presence of Mg 2ϩ (12,23,27,30,37,41). Therefore, we conducted the systematic analysis of the structure/activity relationships of inhibitors in the presence of Mn 2ϩ .…”
Section: Potent and Selective Ac Inhibition By Mant-itp␥s Relative Tomentioning
confidence: 99%
See 1 more Smart Citation
“…Modeling was performed with SWISS-MODEL (Kopp and Schwede 2006) and Phyre (Kelley et al 2000). The extracellular, kinase-like, and guanylate cyclase domains were modeled using a hormone-bound atrial natriuretic peptide (ANP) receptor (NPR)-A extracellular domain (Protein Data Bank ID code 1t34; Ogawa et al 2004), Raf proto-oncogene serine/threonine-protein kinase (1uwj; Wan et al 2004), and type II adenylyl cyclase (1cul; Tesmer et al 2000) as their templates, respectively. The root mean square of distances between the template (real structure) and target (model structure) were 1.4, 0.5, and 1.3 Å (10 −10 m) for extracellular, kinase-like, and guanylate cyclase domains, respectively.…”
Section: Molecular Modelingmentioning
confidence: 99%
“…Adenosine and its derivatives (e.g. 2′,5′-dideoxyadenosine), acting through the P-site, appear to be physiological inhibitors of adenylyl cyclase activity (Tesmer et al, 2000). (Tang et al, 1991), PKC-evoked phosphorylation (Jacobowitz et al, 1993) Gbg (Taussig et al, 1993), PKC-evoked phosphorylation (Chen and Iyengar, 1993;Lustig et al, 1993) Ca 2+ /CaM (Choi et al, 1992), PKC-evoked phosphorylation (Jacobowitz et al, 1993) Gbg (Gao and Gilman, 1991) PKC-evoked phosphorylation (Kawabe et al, 1994) Endogenous inhibitors…”
Section: Anaphylatoxinmentioning
confidence: 99%